A Deep Eutectic Solvent‐Based Approach to Intravenous Formulation. Issue 18 (5th August 2021) - Kim, Jayoung; Shi, Yujie; Kwon, Christopher J.; Gao, Yongsheng; Mitragotri, Samir
Abstract: Clinically viable formulations of hydrophobic drugs, for example, chemotherapeutics, require strategies to promote sufficient drug solubilization. However, such strategies often involve the use of organic solvents that pose a significant risk in generating toxic, unstable products. Using verteporfin as a drug, a deep eutectic solvent (DES)‐based approach to solvate drugs in a simple one‐step process is reported. Lipoidal DES composed of choline and oleate is used to successfully solvate verteporfin, resulting in stable sub‐100 nm nanocomplexes. The nanocomplexes successfully demonstrate efficient cellular uptake as well as retention, tumor spheroid penetration, and tumor accumulation in vivo. Systemic administration of the formulation significantly inhibits the primary tumor growth and its lung metastasis in the orthotopic 4T1 murine breast tumor model. Collectively, biocompatible DES shows great potential as a novel material for intravenous formulation of chemotherapeutics. Abstract : Deep eutectic solvent (DES) is introduced as a novel, biocompatible agent for dissolving water‐insoluble drugs. DES comprised of choline and oleate demonstrates high aqueous solubility of a model chemotherapeutic drug verteporfin via nanocomplexation, and exhibits the ability to overcome multiple biological barriers to achieve successful cancer therapy in vivo against metastatic breast tumor in mice.